Social trematode parasites increase standing army size in areas of greater invasion threat. (26th February 2020) - Resetarits, Emlyn J.; Torchin, Mark E.; Hechinger, Ryan F.
Abstract : Organisms or societies are resource limited, causing important trade-offs between reproduction and defence. Given such trade-offs, optimal allocation theory predicts that, for animal societies with a soldier caste, allocation to soldiers should reflect local external threats. Although both threat intensity and soldier allocation can vary widely in nature, we currently lack strong evidence that spatial variation in threat can drive the corresponding variation in soldier allocation. The diverse guild of trematode parasites of the California horn snail provides a useful system to address this problem. Several of these species form colonies in their hosts with a reproductive division of labour including a soldier caste. Soldiers are non-reproductive and specialized in defence, attacking and killing invading parasites. We quantified invasion threat and soldier allocation for 168 trematode colonies belonging to six species at 26 sites spread among 10 estuaries in temperate and tropical regions. Spatial variation in invasion threat was matched as predicted by the relative number of soldiers for multiple parasite species. Soldier allocation correlated with invasion threat at fine spatial scales, suggesting that allocation is at least partly inducible. These results may represent the first clear documentation of a spatial correlation between allocation to any type of caste and a biotic selective agent.